Studying the relationship between buckwheat (Fagopyrum esculentum Möench) seeds with different morphometric characteristics in response to germination temperatures - Bahman Ahmadvand; Seyed Amir Moosavi; Seyed Ata Siadat; Reza Tavakkol Afshari; Ali GHATEI (علوم و فناوری بذر ایران)
The aim of this study was to investigate the relationship between the morphometric characteristics of the seeds of different buckwheat (Fagopyrum esculentum Möench) lots obtained from different planting dates (29th Aug: 1, 13th Sep: 2, 28th Sep: 3 and 12th Oc: 4) with its seed germination quality under different temperature treatments. For each of seed lot, four separate experiments with 11 temperature levels including 4, 7, 10, 15, 20, 25, 30, 35, 37, 40 and 45 °C were carried out in a completely randomized design with 3 replications in seed science and technology laboratory of Agricultural Sciences and Natural Resources of Khuzestan University in 2022. The results of analysis of variance demonstrated that temperature has a significant effect at the level of 1% on germination rate index. According to the model parameters and of course the standard error, the segmented model was chosen as the best model. Based on this, according to the superior (segmented) model, the base, optimal and ceiling temperatures for lot 1 are 4.82, 34.24 and 44.82 degrees Celsius respectively, in lot 2 they are 4.18, 33.82 and 46 respectively. 44.0 degrees Celsius, in lot 3 it was estimated 5, 34.64 and 43.87 degrees Celsius respectively and in lot 4 it was estimated 5, 31.69 and 44.27 degrees Celsius respectively. Identify the cardinal temperatures can be of great help in managing the optimal sowing date of crops.